Polypharmacy and Potentially Inappropriate Medication Use in Older Blacks with Diabetes Mellitus Presenting to the Emergency Department. (August 2022) - Nightingale, Ginah; Scopelliti, Emily M.; Casten, Robin; Woloshin, Monica; Xiao, Shu; Kelley, Megan; Chang, Anna Marie; Hollander, Judd E.; Leiby, Benjamin E.; Peterson, Andrew M.; Pizzi, Laura T.; Rising, Kristin L.; et al.
Background: Medication-related problems in older Blacks with diabetes mellitus (DM) are not well established.Objectives: To describe the frequency of medication-related problems in older Blacks with DM presenting to the emergency department (ED).Methods: The study was a cross-sectional analysis of baseline data from a randomized controlled trial evaluating Blacks aged ≥60 years of age presenting to the ED. Polypharmacy, potentially inappropriate medication (PIM) use, and anticholinergic score were evaluated.Results: Of 168 patients (median age = 68, range 60–92), most ( n = 164, 98%) were taking ≥5 medications, and 67 (39.9%) were taking a PIM. A majority ( n = 124, 74%) were taking a medication with an anticholinergic score ≥1. Number of medications was correlated with number of PIMs ( r = .22, p = .004) and anticholinergic score ( r = .50, p < .001).Conclusion: Polypharmacy and PIM use was common in older Blacks with DM.